2018
DOI: 10.1504/jibed.2018.095173
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, dynamic capabilities and family firms operating in an emerging economy

Abstract: Innovation, dynamic capabilities and family firms operating in an emerging economy http://researchonline.ljmu.ac.uk/id/eprint/9782/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Alonso, AD, O'Brien, S and Kok, SK (2018) Innovation, dynamic capabilities and family firms operating in an emerging economy. Journal for International Business and Entrepreneurship Development, 11 (3). pp. 221-242. ISSN 1549-9324 LJMU Research Online Innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…These findings, in line with DL theory, show how respondents' in-depth knowledge of the competitive environment facilitated the selection of information relevant to the company and the introduction of innovations, such as BCT, which helped to improve company performance (Alonso et al, 2018;Wong et al, 2019).…”
Section: Dominant Logic and The Managers' Market Visionsupporting
confidence: 71%
See 3 more Smart Citations
“…These findings, in line with DL theory, show how respondents' in-depth knowledge of the competitive environment facilitated the selection of information relevant to the company and the introduction of innovations, such as BCT, which helped to improve company performance (Alonso et al, 2018;Wong et al, 2019).…”
Section: Dominant Logic and The Managers' Market Visionsupporting
confidence: 71%
“…These characteristics filter out the information that is only relevant to the business and which leads the business to redefine its internal strategies (Francisco and Swanson, 2018). As Alonso et al (2018) stated, the owners' knowledge from previous generations is the basis of the selection process of market information and is related to the investments in technology and equipment. Moreover, with reference to the introduction of BCT, the DL perspective demonstrates the strategic role of winery managers to support and sustain the flexibility and distribution of their firms' internal and external knowledge (Pan et al, 2019), which the manager of Ricci Curbastro defined as "ordinary processes", and to endorse the activation of dynamic external relationships (Warner and Wäger, 2019;Morkunas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of research focusing on this study’s main areas, a recent study provides clear links between the dynamic capabilities approach and family firms’ innovating strategies. Duarte Alonso et al (2018) investigated model family firms that have existed for numerous decades. Duarte Alonso et al ’s (2018) study revealed the value of assimilating information, as well as in integrating processes and technologies (sensing), applying information, improving tasks and building alliances (seizing), as well as the significance of updating, learning, modernising and identifying new trends (transforming/reconfiguring).…”
Section: Discussionmentioning
confidence: 99%